2013
DOI: 10.1190/int-2013-0025.1
|View full text |Cite
|
Sign up to set email alerts
|

Integration of surface seismic, microseismic, and production logs for shale gas characterization: Methodology and field application

Abstract: Technologies such as horizontal drilling and multistage hydraulic fracturing are central to ensuring the viability of shale oil and gas resource development by maximizing contact with the most productive reservoir volumes. However, characterization efforts based on the use of well logs and cores, although very informative, may be associated with substantial uncertainty in interwell volumes. Consequently, this work is centered around the development of a predictive tool based on surface seismic data analysis to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…Although hydraulically induced fractures can propagate through ductile and brittle rocks, the goal of the proppant is to better preserves induced fractures in more brittle rocks. Alzate (2012) combines production logs and microseismic data with simultaneous seismic inversion attributes to analyze completion effectiveness along four horizontal wells in the Barnett Shale. He concludes that the hydraulically generated fractures preferentially grow toward the more brittle rock, generating a difference in gas production.…”
Section: Introductionmentioning
confidence: 99%
“…Although hydraulically induced fractures can propagate through ductile and brittle rocks, the goal of the proppant is to better preserves induced fractures in more brittle rocks. Alzate (2012) combines production logs and microseismic data with simultaneous seismic inversion attributes to analyze completion effectiveness along four horizontal wells in the Barnett Shale. He concludes that the hydraulically generated fractures preferentially grow toward the more brittle rock, generating a difference in gas production.…”
Section: Introductionmentioning
confidence: 99%
“…The brittle and rich TOC zones are also marked from the correlation of elastic parameters in cross-plots . Alzate (2012) and Alzate and Devegowda (2013) observed that variation in Young's modulus (E) is a consequence of TOC. Based on their concepts, three zones can be identified within the Patala Track 1 (DT4P -P-wave Sonic log, DT4S -S-wave Sonic Log); Track 2 (VSH -Volume of shale); Track 3 (VP -P-wave velocity, VS -S-wave velocity estimated by using the relationship of Han et al, 1986); Track 4 (IP -P-wave acoustic impedance, IS -S-wave acoustic impedance); Track 5 (PR -Poisson's ratio, E -Young's modulus); Track 6 (TNPH -Neutron porosity, PHIT -Average porosity); Track 7 (B -Brittleness Index); and Track 8 (K -Permeability).…”
Section: Petroelastic and Petrophysical Resultsmentioning
confidence: 99%
“…These parameters are known as "dynamic". The first step on our workflow is mainly calibration of the static-to-dynamic relationship in order to then apply such as relationship to the dynamic well log data Once this correction is applied, the integration of the parameters is done by using a rock mechanics template (RMT) modified after Alzate (2012), where a series of regions had been discriminated in terms of mechanical behaviour and TOC content. After this analysis is done using well log data, this region has been applied in a 3D fashion onto a seismic cube.…”
Section: Methodsmentioning
confidence: 99%